Evaluation of Antibiotic Resistance and Virulence Factors of Escherichia coli Strains Isolated from Cancer Patients - jalal, belan jamal; Kareem, Banaz Omer (Journal of Sulaimani Medical College, 2026)
Background: Cancer patients are highly susceptible to infections. Extraintestinal pathogenic E. coli (ExPEC) often exhibit multidrug resistance (MDR) and harbour virulence factors that increase pathogenicity. Objectives: This study aimed to evaluate the antibiotic resistance patterns and the prevalence of virulence genes (fimH, traT, and hlyA) in E. coli isolates from cancer patients. Methods: The study included E. coli isolates (n = 50) collected from various clinical specimens of cancer patients, between September and December 2024 at Hiwa Hematology and Oncology Hospital, in Sulaymaniyah, Iraq. An antibiotic susceptibility test was conducted to assess the bacterial resistance profile, and Polymerase Chain Reaction (PCR) was used to identify virulence genes. Results: MDR was identified in 72%, and high levels of resistance were observed against β-lactam antibiotics, particularly ampicillin and ceftriaxone. Fluoroquinolone resistance among isolates was notably high, especially to Ciprofloxacin and Levofloxacin. Amikacin and Gentamicin were identified as suitable antibiotics for treating E. coli infection. Among the virulence genes, fimH was the most frequently detected (100%), then traT, and hlyA. Phenotypically, only one isolate demonstrated hemolytic activity on blood agar, indicating its ability to lyse red blood cells. There was no significant relationship found between antibiotic resistance and the presence of virulence genes. Conclusion: The results demonstrate that cancer patients are exposed to diverse strains of E.coli that possess both antimicrobial resistance and disease-causing potential, underscoring the importance of improving monitoring, prevention, and treatment strategies for E. coli infections within this vulnerable group.
Keywords: Antibiotic resistance; cancer patients; Escherichia coli; virulence genes; urinary tract infection